indonesia: BUILDING CONSUMER LOYALTY ON THE ONLINE BUYING PLATFORM THROUGH CONSUMER SATISFACTION INFLUENCED BY THE PERCEIVED EASE OF USE - Wibowo, M. Haroldio Apsan; Djuardi, Dian Komarsyah; Djausal, Gita Paramita (Jurnal Kompetitif Bisnis, 2021)
In the midst of intense e-commerce competition in Indonesia, companies engaged in online buying and selling platforms such as Shopee, Tokopedia, Lazada and others must compete to win consumer loyalty in order to survive in the e-commerce industry sector in Indonesia. The purpose of this research was to determine the influence of perceived ease of use on consumer loyalty mediated by consumer satisfaction who shopped using Shopee application The number of respondents in this research were 400 people. The data analysis of this research used path analysis. The results of this research indicate that partially and simultaneously perceived convenience have a significant effect on customer satisfaction, partially and simultaneously perceived ease of use and customer satisfaction have a significant effect on consumer loyalty.